Inovasi Pangan Fungsional Berkelanjutan: Snack Bar Kaya Kalsium Berbasis Tepung Limbah Cangkang Telur Ayam Ras: Sustainable Functional Food Innovation: Calcium-Rich Snack Bar Based on Waste Flour from Layer Chicken Eggshells - Samsul, Erwin; Handayani, Yeni Fitri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2026)
Calcium is an essential mineral that plays a crucial role in bone health, neuromuscular function, and cellular metabolism. Insufficient calcium intake can increase the risk of osteoporosis and other metabolic disorders, while the trend of consuming healthy snacks and functional foods continues to rise in modern society. Innovative and environmentally friendly sources of calcium are needed to meet nutritional needs while reducing agro-industrial waste. Waste flour from layer chicken eggshells is a natural source of calcium carbonate with high potential for food product fortification, but research utilizing this waste is still limited. This research aims to formulate snack bars with flavor variations based on waste flour from layer chicken eggshells as a healthy and functional alternative source of calcium nutrition. The research methods include the process of making eggshell flour thru the stages of cleaning, drying, and grinding, followed by formulating snack bars using several flavor variations. The resulting product is evaluated based on physical and organoleptic characteristics, as well as an analysis of calcium content. The result of the rating test show that the most preferred attribute for the red bean variant (F1) is color (5.64), for the chocolate variant (F2) it is aroma (5.97), and for the cheese variant (F3) it is overall evaluation (5.97). Based on the ranking test results, the chocolate variant (F2) received the highest raning and was the most preferred variant by the panelists overall. The results of the calcium content analysis test, as well as the organoleptic evaluation and acceptability, showed that the chocolate-flavored snack bar was the most preferred in terms of taste, aroma, and texture. The calcium content obtained was 0.34%. Proximate analysis showed a moisture content of 9.92%, ash 3.25%, acid-insoluble ash 0.60%, protein 13%, fat 15.75%, and carbohydrates 58.08%. This indicates that using broiler chicken eggshell flour in snack bar formulations can provide added nutritional value and has the potential to be developed as a sustainable healthy functional snack product. Keywords: Calcium, Chicken Eggshell, Snack Bar, Healthy Functional Snack Abstrak Kalsium merupakan mineral esensial yang berperan penting dalam kesehatan tulang, fungsi neuromuskular, dan metabolisme seluler. Kekurangan asupan kalsium dapat meningkatkan risiko osteoporosis dan gangguan metabolik lainnya, sementara tren konsumsi pangan sehat (healthy snack) dan pangan fungsional (functional food) terus meningkat di masyarakat modern. Sumber kalsium yang inovatif dan ramah lingkungan diperlukan untuk memenuhi kebutuhan nutrisi sekaligus mengurangi limbah agro-industri. Tepung limbah cangkang telur ayam ras merupakan sumber kalsium karbonat alami yang memiliki potensi tinggi untuk difortifikasi dalam produk pangan namun untuk penelitian dengan memanfaatkan limbah ini masih terbatas. Penelitian ini bertujuan untuk memformulasikan snack bar dengan variasi rasa berbasis tepung limbah cangkang telur ayam ras sebagai alternatif sumber nutrisi kalsium yang sehat dan fungsional. Metode penelitian meliputi proses pembuatan tepung cangkang telur melalui tahapan pembersihan, pengeringan, dan penghalusan, dilanjutkan dengan formulasi snack bar menggunakan beberapa variasi rasa. Produk yang dihasilkan dievaluasi berdasarkan karakteristik fisik, organoleptik, dan analisi kandungan kalsium. Hasil rating test menunjukkan bahwa atribut yang paling disukai pada varian kacang merah (F1) adalah warna (5,64), pada varian cokelat (F2) adalah aroma (5,97), dan pada varian keju (F3) adalah penilaian keseluruhan (overall) 5,97. Berdasarkan hasil ranking test, varian cokelat (F2) memperoleh peringkat tertinggi dan menjadi varian paling disukai panelis secara keseluruhan. Hasil uji analisis kandungan kalsium serta penilaian organoleptik dan daya terima menunjukkan hasil bahwa snack bar rasa cokelat paling disukai dari segi rasa, aroma dan tekstur. Kadar kalsium yang diperoleh sebesar 0,34%. Analisis proksimat menunjukkan kadar air 9,92%, abu 3,25%, abu tidak larut asam 0,60%, protein 13%, lemak 15,75%, dan karbohidrat 58,08%. Hal ini menunjukkan bahwa penggunaan tepung cangkang telur ayam ras pada formulasi snack bar dapat memberikan nilai tambah nutrisi serta potensi untuk dikembangkan sebagai produk healthy functional snack yang sustainable. Kata Kunci: Kalsium, Cangkang Telur Ayam Ras, Snack Bar, Healthy Functional Snack